To solve the quadratic equation \( 46x^2 - 138x = 0 \) by factoring out the greatest common factor (GCF), we first identify the GCF of the terms.
The two terms are \( 46x^2 \) and \( -138x \). The GCF of the coefficients \( 46 \) and \( -138 \) is \( 46 \), and both terms contain at least one \( x \). Therefore, the GCF is \( 46x \).
Now we can factor out \( 46x \) from the equation:
\[ 46x^2 - 138x = 46x(x - 3) = 0 \]
Now we have the factored equation:
\[ 46x(x - 3) = 0 \]
Next, we set each factor to zero to find the solutions:
-
\( 46x = 0 \) \[ x = 0 \]
-
\( x - 3 = 0 \) \[ x = 3 \]
Therefore, the solutions to the equation \( 46x^2 - 138x = 0 \) are:
\[ x = 0 \quad \text{and} \quad x = 3 \]